Pengaruh Kualitas Produk Dan Harga Terhadap Kepuasan Pelanggan Pada Ayam Geprek Di Bekasi Timur - Intan Adilah Nasution; Hadita Hadita (Journal of Management and Creative Business, 2024)
The objectives of this research are: The influence of product quality on customer satisfaction with Geprek chicken in Bekasi Timur, the influence of price quality on customer satisfaction with Geprek chicken in Bekasi Timur, the influence of product quality and price quality on customer satisfaction with Geprek chicken in Bekasi Timur. This research is a questionnaire survey. The sampling technique was purposive sampling with a sample size of 15 people. The data collection technique uses a questionnaire whose validity and reliability have been tested. The data analysis technique used is multiple regression. The results of this research show that product quality and price have a significant effect on customer satisfaction at Ayam Geprek in Bekasi Timur.